Causes of Shadow Banking - Two Regimes of Credit Risk Transformation and its Regulation - Raphael Flore (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper presents of a model of banking in order to study why different agents may prefer a 'regulation by the market' over the regulation by a governmental agency, and it illustrates the interaction of two sectors regulated in such alternative ways. Financial intermediaries can operate either as commercial bank, which is regulated by an agency that also insures its deposits, or as uninsured 'shadow bank' whose leverage is constrained by the risk-aversion of investors. The analysis shows that there are exactly three possible reasons for choosing shadow banking: First, lower operational costs, second, heterogeneous beliefs about the aggregate risk, and third, the sponsoring of shadow banks by commercial banks. Heterogeneous beliefs lead to a self-selection of optimistic depositors and pessimistic intermediaries into shadow banking, with the latter profiting from the optimism of the former. Sponsored shadow banking impairs the solvency of the sponsor in downturns, but it is more profitable than independent shadow banking. It does not only allow for a shift to a system 'regulated by markets', but it allows for multiplicative leverage owing to the combination of two balance sheets. It is an unambiguous sign of regulatory arbitrage, as it becomes unprofitable if the regulation is adjusted to avoid contagion.
Keywords: G21; G23; G28; 330